Tahfiz (memorization Sciences) Curriculum Practice: An Empirical Study From Private School in Johor, Malaysia - Abd Rahman Abd Ghani; Miftachul Huda; Maidatus Sholihah; Tabrani ZA; Hayati Hussin (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2025)
Indexed by WOS/Scopus/ERA